Dynamics of amplification in a nanoplasmonic metamaterial - Wuestner, S.; Pusch, A.; Hamm, J.M.; K. L. Tsakmakidis; Hess, O. (Applied Physics A: Materials Science and Processing, 2012)
Plasmonic metamaterials form an exciting new class of engineered media that promise a range of important applications, such as subwavelength focusing, cloaking and slowing/stopping of light. Recently it has been shown that the internal losses due to the natural absorption of metals at optical frequencies can be compensated by gain. Here, we employ a Maxwell-Bloch methodology which allows us to study the dynamics of the coherent plasmon-gain interaction, nonlinear saturation, field enhancement and radiative damping. Using numerical pump-probe experiments on a double-fishnet metamaterial with dye-molecule inclusions we investigate the buildup of the inversion and the formation of the plasmonic modes in the low-Q fishnet cavity. We find that loss compensation occurs in the negative-refractive-index regime and that, due to the loss compensation and the associated sharpening of the resonance, the real part of the refractive index of the metamaterial becomes more negative compared to the passive case. Furthermore, we investigate the behavior of the metamaterial above the lasing threshold, and we identify the occurrence of a far-field lasing burst and gain depletion. Our results provide deep insight into the internal processes that affect the macroscopic properties of active metamaterials. This could guide the development of amplifying and lasing plasmonic nanostructures. © 2012 Springer-Verlag.